Serverless Data Engineering: Revolutionizing Retail and Finance Industries - Raghavendra Gandhi Raketla, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Serverless computing has revolutionized data engineering, transforming how organizations design and implement their data processing architectures. This comprehensive article explores the evolution, implementation patterns, and best practices of serverless data engineering, with a particular focus on retail and financial services sectors. The article examines the technical foundations, including event-driven architectures, compute layers, and storage infrastructures, while presenting detailed case studies from industry leaders. This article shows real-world implementations, the research demonstrates how serverless architectures enhance operational efficiency, reduce infrastructure costs, and improve system performance. The article covers advanced topics such as customer analytics pipelines, fraud detection systems, and regulatory compliance frameworks, providing insights into both technical and business aspects of serverless adoption.
Keywords: Serverless Computing; Data Engineering; Cloud Architecture; Event-Driven Processing; Infrastructure Optimization